A Comparison of Undergraduate Students’ Self-Efficacy in English Communication of the Faculty of Hospitality Industry, Kasetsart University, Kamphaeng Saen Campus - Yusamran, Patpinan; Chayaban, Waranyu (Sripatum Review of Humanities and Social Sciences, 2026)
This research aimed to (1) analyze the level of students’ self-efficacy in English communication in terms of listening, speaking, reading, and writing. and (2) compare students’ self-efficacy in English communication classified by gender and academic year. The samples were 405 undergraduate students from the Faculty of Hospitality Industry, Kasetsart University, Kamphaeng Saen Campus, selected through stratified random sampling. The research instrument was a five-point Likert-scale questionnaire, which demonstrated excellent content validity (S-CVI = 0.97), strong construct validity by CFA (χ² = 0.407, df = 1, p = 0.524, CFI = 1.00, TLI = 1.00, SRMR = 0.002, RMSEA < 0.01), and the overall reliability of the instrument, as measured by Cronbach’s alpha coefficient, was 0.985. Data were analyzed using mean and two-way analysis of variance (ANOVA). The results revealed that students reported moderate levels of self-efficacy in reading and listening, but low levels in speaking and writing. Among the four skills, reading showed the highest mean score (M = 3.00), followed by listening (M = 2.68), speaking (M = 2.53), and writing (M = 2.30), respectively. Moreover, there was no significant interaction effect between gender and academic year on overall English communication self-efficacy (p = .223). Gender (p = .180) and academic year (p = .179) also showed no significant main effects on students’ overall self-efficacy in English communication.